Clinical Experience with Frameless Neuronavigation Guided Biopsy for Intracranial Space Occupying Lesion - Thulung, Suraj; Bishokarma, Suresh; Lohani, Subash; Shrestha, Dinuj; Aryal, Binit; Napit, Munu (Nepal Journal of Neuroscience, 2019)
Biopsy is mandatory for histological diagnosis of non-resectable brain tumors. Of various techniques, neuronavigation guided biopsy provides intraoperative real-time reference and allows biopsy from multiple trajectories. The aim of this study is to assess the efficacy and accuracy of frameless neuronavigation biopsy. We retrospectively reviewed the medical archives of patients with intracranial space occupying lesion who underwent frameless neuronavigation biopsy at our institute between 2016 to 2018. All operations were performed under general anesthesia. Data were analyzed by SPSS version 20. P value of <0.05 was considered significant. There were 46 patients who underwent neuronavigation guided biopsy over the period of two years. Median age of patients was 46.5 years. Supratentorial tumors accounted for 95.8% of cases. Mean tumor diameter was 3.35 cm. Accuracy was 89.1%. More than half were glial tumors. Histopathology was inconclusive in 10.9% cases. Complication rate was 4.3%: one tract hematoma and one new neurological deficit. Frameless neuronavigation guided biopsy of intracranial space occupying lesion is safe and efficacious procedure with high diagnostic yield.